2011
DOI: 10.1007/s00113-011-1975-0
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Evaluation des PFNA® und Zusammenhang zwischen Tip-Apex-Distanz und mechanischem Versagen

Abstract: The incidence of trochanteric fractures is increasing in Europe, and the economic impact and mortality is high. The aim of the study was to evaluate the PFNA® (proximal femoral nail antirotation) with respect to its clinical use and mechanical complications.All patients with a trochanteric fracture who had been treated with a PFNA® between 12/2004 and 12/2007 were identified and analysed regarding complications and radiological findings. The study included 195 patients; 61.2% of the patients were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Furthermore, we did not test the impact of the improved accuracy in terms of an optimized TSD on the strength of fixation as our intent was to study the effect of the ADAPT system on the accuracy of implant placement. However, several studies analysed the correlation of the TAD and the likelihood of a cut-out [10,12,14,15,20-22]. Further biomechanical or clinical studies should be undertaken to investigate whether these findings can be extrapolated to the TSD measurement and whether the TSD proves useful as an intraoperative assessment tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we did not test the impact of the improved accuracy in terms of an optimized TSD on the strength of fixation as our intent was to study the effect of the ADAPT system on the accuracy of implant placement. However, several studies analysed the correlation of the TAD and the likelihood of a cut-out [10,12,14,15,20-22]. Further biomechanical or clinical studies should be undertaken to investigate whether these findings can be extrapolated to the TSD measurement and whether the TSD proves useful as an intraoperative assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that increasing TAD above 25 mm was strongly correlated with an increased risk of lag screw cut-out through the femoral head. Several other studies supported this conclusion, showing that the TAD is a highly significant predictor of mechanical failure due to cut-out [10,12,14,15,21,22]. In a later study, Pervez et al recommended a TAD of less than 20 mm [21].…”
Section: Introductionmentioning
confidence: 93%
“…Given the gravity of the event, it is important to determine risk factors which contribute to and are associated with implant failure. Kraus et al 11 reported that tip-apex-distance (TAD) greater than 30 mm was the main risk factor. Turgut et al 12 believed that if the coxa vara cannot be corrected, the lag screw will be in a unfavorable position.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of proximal femur fractures has improved due to new implant designs in recent years [1, 2]. However, postoperative complication rates resulting from the procedure of up to 10.7% are still reported [3].…”
Section: Introductionmentioning
confidence: 99%